2021
DOI: 10.1007/s12031-021-01832-8
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin C Promotes Glioma Cell Malignant Behavior and Inhibits Chemosensitivity to Paclitaxel via Activation of the PI3K/AKT Signaling Pathway

Abstract: The present study aimed to detect the effect of tenascin C (TNC) on cell function and chemosensitivity to paclitaxel and phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling in glioma cells.Human glioma cells U87, LN-229, T98G and U251 and normal human astrocytes were obtained, in which TNC expression was detected. The U87 cells and U251 cells were chosen and infected with lentivirus of control overexpression, TNC overexpression, control knockdown, and TNC knockdown for functional experiments. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(33 reference statements)
1
10
0
1
Order By: Relevance
“…The results showed that the depletion of TNC expression significantly attenuated the proliferation and migration abilities of the NSCLC cell lines. It has been found that the function of TNC is linked to the activation of the AKT signaling pathway, 37,38 we also found a reduction in the pAKT-Ser473 signal in the TNC-depleted cells. If TNC was the major downstream effector of EN2, we would be able to observe the similar phenomenon in EN2-PC9 and EN2-A549 cells.…”
Section: The Tnc-akt Axis Has a Critical Role In En2mediated Oncogeni...supporting
confidence: 71%
“…The results showed that the depletion of TNC expression significantly attenuated the proliferation and migration abilities of the NSCLC cell lines. It has been found that the function of TNC is linked to the activation of the AKT signaling pathway, 37,38 we also found a reduction in the pAKT-Ser473 signal in the TNC-depleted cells. If TNC was the major downstream effector of EN2, we would be able to observe the similar phenomenon in EN2-PC9 and EN2-A549 cells.…”
Section: The Tnc-akt Axis Has a Critical Role In En2mediated Oncogeni...supporting
confidence: 71%
“…Globally, well known for the high probability of metastasis and recurrence, glioma is still a leading cause of mortality in brain tumors [ 20 ]. Despite advances in the diagnosis of glioma, most glioma patients can only be diagnosed at the intermediate and advanced stages when surgical resection is not an optimal option [ 21 ]. Therefore, accurate patient stratification based on reliable prognostic factors is essential for the decision of clinical management and the determination of a subset of glioma patients suitable for personalized treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, well known for the high probability of metastasis and recurrence, glioma is still a leading cause of mortality in brain tumors 20 . Despite advances in diagnosis of glioma, most glioma patients can only be diagnosed at the intermediate and advanced stage when surgical resection is not an optimal option 21 .…”
Section: Discussionmentioning
confidence: 99%